Mental Health Promotion through training for voluntary agents in the workplace. A longitudinal study - Gascón-Santos, Santiago; Xiaoxia, Yang; Pérez-Montesinos, Yago; Fueyo-Díaz, Ricardo; Alacreu-Crespo, Adrián; Aguilar-Latorre, Alejandra; Irigoyen-Recalde, Isabel (Acciones e Investigaciones Sociales, 2025)
Introduction: This study assessed the benefits of implementing a network of mental health promoters within organizations, focusing on staff training and the establishment of exchange and follow-up groups. The aim was to improve working conditions, facilitate early detection of psychological symptoms, provide support techniques, guide employees to health services, and promote overall well-being. Material and Methods: The study involved 685 employees from 22 companies (477 in the intervention group and 208 in the control group). Instruments used included: 1) Demographic and occupational data form; 2) General Health Questionnaire (GHQ-12); 3) Five items from The Columbia-Suicide Severity Rating Scale; 4) Maslach Burnout Inventory (MBI General Survey). Results: The intervention group showed significant improvements in depersonalization and personal accomplishment compared to the control group. Notable differences were also found in General Health, depersonalization, and personal accomplishment between the two groups. Conclusion: The implementation of a network of mental health promoters in organizations effectively enhanced key aspects of employees’ psychological well-being, highlighting the value of structured and sustainable interventions for promoting mental health in the workplace.